Polymorphism of delta-aminolevulinic acid dehydratase and its effect on blood lead levels in thai workers - Winai Wananukul (2018)
To determine the prevalence of delta-aminolevulinic acid dehydratase (ALAD) polymorphism and its effects on blood lead levels (BLLs) in Thai workers, the authors performed a cross-sectional analysis of 389 Thai workers who were exposed to lead in a battery plant. The authors collected blood for BLLs and genotypic study, and they found that the allele frequencies of ALAD1 and ALAD2 were 0.98 and 0.02, respectively. They made a comparison of BLLs between genotype by dividing the levels into 2 categories of lead exposure (high and medium magnitude of exposure) and using length of employment as a covariance. Their results showed no significant difference of BLLs between the ALAD1-1 and ALAD1-2/ALAD2-2 groups in both levels of exposure. The frequency of ALAD2 in Thai workers was low; the authors found that ALAD polymorphism had a small or only modest effect on BLLs. © 2007 Heldref Publications.